Understanding perceived effectiveness of a novel coastal management project: The case of the Bacton-Walcott sandscaping scheme, UK - Cotton, Isabel; Forster, Johanna; Lorenzoni, Irene; Tolhurst, Trevor J. (Frontiers in Marine Science, 2022)
Adaptation at actively receding coastal areas requires swift and long-term solutions that build resilience for both people and the environment. Nature-based solutions are increasingly being promoted over hard defences, but there is a lack of empirical research on the effectiveness of novel approaches, including those deployed at different scales. Sandscaping, a one-off large-scale deposition of sand (1.8 M m3) on a beach frontage, was implemented for the first time in the UK at a section of beach between Bacton and Walcott villages, in North Norfolk, in 2019. The purpose of sandscaping in this location was primarily to protect the nationally important gas terminal, and neighbouring villages from coastal erosion and flooding. This study investigates the perceived effectiveness and impacts of sandscaping on coastal residents, by eliciting views of residents in the two closest villages to the scheme, and comparing findings to geomorphological observations (using LiDAR data). A survey of Bacton and Walcott residents was distributed in January 2022, with n=77 responses. Results reveal wide differences in perceptions, and notable levels of doubt, on the ‘effectiveness’ of sandscaping at present and in the future, alongside different lived experiences of the scheme and prevailing distrust by some residents about coastal management. Keeping residents updated on changes to sandscaping with environmental data and communicating the advantages of nature-based solutions appear relevant in this context, but the diversity and contrast of resident perceptions illustrates deeper challenges for future coastal management planning. There is a need to think through how future coastal change can be planned for, drawing upon multiple social perspectives. This paper also illustrates that ‘effectiveness’ of sandscaping should be more widely examined in relation to the experiences and perspectives of those impacted by the scheme, and beyond evaluations of geomorphological change.